Assessment of the capacity, incentives, and performance of agricultural extension agents in western Democratic Republic of the Congo - Ragasa, Catherine; Ulimwengu, John M.; Randriamamonjy, Josee; Badibanga, Thaddée (International Food Policy Research Institute, 2013)
This paper provides an in-depth review of the agricultural extension system of DRC including an analysis of its policies and legal framework, organization, and management; links to critical institutions; and capacity and incentive of different actors in the system. This review involved document analyses, interviews with key informants, and surveys of 107 extension organizations and 162 extension agents in 156 randomly selected villages in western DRC. This review suggests serious funding constraints, human resource management problems, no linkage and coordination within the extension system and with research and education systems, and a majority of underserved communities and farmers. This review also highlights a good opportunity given the huge human resources (more than 11,000 agents) deployed into the sectors and territories as part of the Ministry’s agricultural inspection system.